A New Lnc in Metastasis: Long Non-Coding RNA Mediates the Pro-metastatic Functions of TGF-β - Li, Wenyang (2014)
TGF-β signaling promotes metastasis by controlling the expression of downstream target genes. In this issue of Cancer Cell, Yuan et al. discover a novel TGF-β-induced lncRNA, lncRNA-ATB, that stimulates EMT through sequestering miR-200s and facilitates colonization by stabilizing IL-11 mRNA, thus promoting both early and late steps of cancer metastasis.